PENAMBAHAN SERAT TANDAN KOSONG KELAPA SAWIT (TKKS) DALAM RANGKA MEREDUKSI BERAT KOMPOSIT PAPAN SEMEN - tarkono - tarkono; Hadi - Ali (ROTOR, 2017)
Inventories of oil palm empty fruit bunches palm (EFBP) at oil palm factories are very abundant. This will be a problem if the handling is not serious. Utilization of EFBP fiber as a technical material is one effort that can be done in order to help reduce the problem of EFBP waste in palm oil mill. EFBP fibers as the substance of fibrous cement board aims to reduce to the weight of the material without lowering its strength. The method of making fibrous cement board by mixing EFBP fiber into dough with 12% marble powder ratio, 10% CaCO3 powder and EFBP fiber volume and portland cement are varied. The addition of EFBP fibers as much as 16% of the total volume can decrease the weight by 15.2%. The results showed that the cement board based on EFBP fibers under optimum conditions has a tensile strength of 1.58 Mpa, density (ρ) of 1519 k g / cm3 and bending strength of 2.61 MPa. Thus, the addition of EFBP fiber to the production of cement board has the potential to be mass produced Keywords : cement board , fibre, EFBP